Relation of Body Mass Index With Fasting Blood Sugar and Triglycerids Level in Healthy Young Adult Medical - Raju, G.M.; V., Vijayanath; Anitha, M.R. (International Journal of Medical Toxicology and Forensic Medicine, 2012)
Background: Now a day’s, high risk habits like smoking, drinking alcohol, stress and sedentary life Prone to develop diabetes mellitus leading to cardiovascular diseases. Material and methods: These are common factors in medical students hence we have taken up this Study. Students of SS Institute of Medical Science and Research Center, Davanagere, Karnataka, were assessed with their consent for anthropometric measures, fasting blood sugar and triglyceride levels. Results: Among 257 students 130 male and female were 127. In 130 male students 11 were underweight with BMI < 19 Kg/m2, 94 were of normal that is their BMI was between 19 Kg/m2 – 26 Kg/m2 and 25 were overweight with BMI of >26 Kg/m2. In 127 female students 21 were underweight with BMI less than 19 Kg/m2, 82 were of normal weight group of BMI between 19 Kg/m2 – 26 Kg/m2 and 24 were in overweight group of BMI more than 26 Kg/m2. Mean BMI of the three groups in the 130 male students was 22.66±3.36 and that of 127 female is 21.36±3.49. Mean fasting blood sugar level in male is 82.25±9.48 mg/dl and in Female 83.03±10.62 mg/dl. Their mean Triglyceride level was in male 95±39.65 mg/dl and in female 96.08±29.66 mg/dl. Conlusion: Present study shows females and males having overweighted and the fasting blood sugar and triglycerides are more in females than males. From Present study we can say that females are more prone to develop CVD and diabetes mellitus than males even though the risk factors are very high in males.